(AUTOMATIC IDENTIFICATION SYSTEM (AIS) SATELIT DATA CORRECTION USING INTERPOLATION AND EXTRAPOLATION METHODE, (Case Study : LAPAN-A2 and LAPAN-A3 Satellite)) - Karim, Abdul; Permala, Rizki; Mukhayadi, M; Hasbi , Wahyudi (BRIN Publishing, 2018)
Nasional Institute Aerounautics and Space (LAPAN) has two satellites (LAPAN-A2 and LAPAN-A3) that are carry Automatic Identification System (AIS) sensors. It can be use for monitoring Indonesian maritime. The altitude of the satellite about 642 Km and 500 km so it has a wide area covered and receive big data. The problem is the AIS technology use the Time Division Multiple Access (TDMA) system that has limitations in handling big data so that some data received can be damaged due to collision. Therefore, in this research has been done the analysis and correction data using interpolation and extrapolation methods. The resultsÂ is improvements of valid data about 22,6 % for LAPAN-A2 satellite and 20,8 % for LAPAN-A3 satellite.